Optimization of high voltage sterilization machine based on dielectric barrier discharge plasma against Salmonella sp. with response surface methodology on (Gallus gallus domesticus) chicken egg. (February 2019) - Widyastuti, E; Mashitoh, D; Yunianta,
Abstract: Egg consumption experiences a substantial growth year by year. But on the other, eggs are susceptible to physical, chemical, or biological damage due to their high nutrients. Biological damage occurs when Salmonella infected eggs while still in the parent body or contamination from the outside. The technology used today to reduce Salmonella is ineffective and takes a long time in the process. Therefore, many new technologies were developed to eliminate Salmonella sp. like plasma technology. Dielectric Barrier Discharge Plasma is an electrical discharge between two separate electrodes with a dielectric insulator. Plasma reactivity can cause oxidative effect on the outer surface of microbial cells. Aim of this research is to determine the optimal condition of sterilization process in egg using sterilization machine based on Dielectric Barrier Discharge Plasma to reduce Salmonella sp. in egg. Central Composite Design in Responses Surface Methodology with two independent variables are Input Voltage and time was used in this research. The results show variable have a significant effect on the response with optimum point of each variable is 26.97 volt for input voltage and 377.64 for time. The optimum condition for reduce Salmonella sp. is 4.98 Log CFU mL −1 . Higher voltages and longer processing times result in much reactive oxygen produced by Dielectric Barrier Discharge Plasma so that microbial reduction is more effective. This research demonstrates the feasibility of Dielectric Barrier Discharge plasma as an intervention to further reduce foodborne pathogens on chicken egg.